ANALISIS PEMANFAATAN INTERNET OLEH GURU DALAM PEMBELAJARAN DI SMK BINA BHAKTI CILACAP - Lusiani Lusiani; Andi Hendrawan; Gilang Meilanda Kurniawan; Supriyanto Supriyanto (Universitas Pahlawan Tuanku Tambusai, 2022)
Teachers generally have their own techniques in using the internet as a learning medium, this is one of the things that triggers learning activities and allows the realization of good learning goals, so the authors are interested in analyzing the use of the internet by teachers in learning at SMK Bina Bhakti Cilacap. This study uses qualitative research methods through descriptive and quantitative approaches. The purpose of the study is to analyze the use of the internet by teachers in learning at SMK Bina Bhakti Cilacap quantitatively and describe it in the form of narrative sentences. The location is at SMK Bina Bhakti Cilacap online with the subject teacher at the school. It was concluded that the internet was used as a complement by teachers in learning at SMK Bina Bhakti Cilacap. Keywords: analysis, internet use, learning